PENGGUNAAN KARYA CIPTA VLOG PADA YOUTUBE OLEH FAKE ACCOUNT: The Usage of Copyright Vlog by a Fake Accountuser on YouTube - Rengkung, Ashley Juniare Maria; Nugrahani, Rr. Aline Gratika (Faculty of Law, Universitas Trisakti, 2024)
Social media has become a platform for many people to express themselves, sharing stories and also a place to find entertainment. Behind the benefits of social media, it does not rule out the possibility of causing negative impacts when using it. For example, as if in the Facebook Platform, there are many violations of the Copyright Law where someone with a Fake Account without the consent of the creator steals thatperson's work and then uploads it again with the aim of taking economic rights from the creator. This research will discuss the use of Vlog by Fake Accounts according to Law Number 28 of 2014 concerning copyright and sanctions given by the Facebook platform to owners of Fake Accounts on its platform. The type of research used is normative legal research with secondary data, which is supported by primary data.The nature of the research is descriptive and conclusions are drawn using deductive reasoning. Based on the research results, it was concluded that many cases of copyright infringement occurred on existing social media, especially Facebook, one of which was the use of Vlog works by Fake Accounts, but in handling this Facebook has community standards which on the facebook.com website specifically